PENINGKATAN KINERJA PENGELOLAAN KAS UMKM SHUTLLECOCK MELALUI IMPLEMENTASI SISTEM INFORMASI KAS (SI-KAS) - Widianto, Andri; Faedah, Yusri Anis; Mahmudah, Nurul; Fuadha, Shafa (Jurnal Abdimas Sangkabira, 2024)
The invested capital is not managed correctly, so the recording of business and personal finances is still mixed. The Cash Information System (Si-Kas) is an information system created to facilitate users in recording finances, both cash receipts and expenditures. This community service method uses the Si-Kas direct practice method. This community service activity concludes that the shuttlecock UMKM will use the Si-Kas application to increase work effectiveness and efficiency.